Effect of graphene reinforcement on hybrid bioceramic coating deposited on the produced porous Ti64 alloys - Aslan, N.; Aksakal, B. (SPRINGER, 2021)
Porous-Ti64 alloys (P-Ti64), produced at various porosities by hot-pressing technique with the help of Mg spacer, were coated by hybrid-Graphene Oxide (rGO) reinforced-hydroxyapatite (HAp), using the sol-gel method. The synthesized rGO powder was used in reinforcing HAp by the Modified Hummers method having 30 mu m particle size and nano (nm) scale layer thickness. Hybrid coatings were executed on Ti64 substrates in four different groups as single-HAp, HAp reinforced with 0.5 wt%, 1.0 wt% and 1.5 wt% rGO for three different porosities (41, 52, and 64%) were characterized by FT-IR, Raman, XRD and SEM. The average 21 mu m coating film thicknesses were obtained and desirably, the only superficial pores of the substrates were closed by coating material rather than the inner connected open pores. It was also shown that 0.5 wt% and 1.0 wt% rGO reinforcements into HAp prevented crack formation on the Ti64 surfaces, whereas 1.5 wt% rGo reinforcement and single-HAp coatings caused. The highest adhesion strength values were achieved at low porosities (41-52%) and of 0.5-1.0 wt% rGO reinforcements through the adhesion tests.
Keywords: Porous Ti64; Sol– gel; Graphene; Hydroxyapatite; Adhesion strength; SOL-GEL; MECHANICAL-PROPERTIES; CALCIUM-PHOSPHATE; TITANIUM; OXIDE; REDUCTION; DISPERSION; OXIDATION; Chemistry; Materials Science